Nutrition Knowledge, Breastfeeding and Infant Feeding Practice of Mothers in Cirebon Regency - Karina Rahmadia Ekawidyani; Ali Khomsan; Mira Dewi; Yughni Azizah Thariqi (Amerta Nutrition, 2022)
Background: Exclusive breastfeeding should be supported by early initiation of breastfeeding (EIBF), provision of colostrum and not providing pre-lacteal feeding.   Objectives: The study objective was to analyze nutritional knowledge and factors related to breastfeeding and feeding practices of lactating mothers. Methods: A cross-sectional study was conducted in March–November 2020 in Sibubut, Kedungdalem, and Bayalangu Kidul Villages, Cirebon Regency. Study respondents were 44 lactating mothers with under six months infants. Mothers’ nutritional knowledge of breastfeeding and breastfeeding/feeding practice were obtained using a validated questionnaire, while the food consumption data of mothers was obtained from two days of 24-hour food recall (weekday and weekend). Spearman’s correlation test and Chi-Square analysis were used to analyze the correlation between variables, while the Mann-Whitney test was used to analyze the difference in nutritional knowledge and breastfeeding/infant feeding practice variables based on education level. Results: Family characteristics (age, mother’s education and occupation, household income, parity, family size, and Body Mass Index (BMI) were not correlated with breastfeeding/infant feeding practice (p=0.427; 0.136; 0.481; 0.056; 0.699; 0.241; 0.547, respectively). There was no significant correlation between nutritional knowledge and breastfeeding/infant feeding practice of mothers (p=0.728). No significant difference was found in the nutritional knowledge of breastfeeding (p=0.828) and breastfeeding/feeding practice of infants (p=0.572) between mothers with education > elementary school and < elementary school. More mothers with low education provided pre-lacteal food than mothers with higher education (p =0.046). Conclusions: The breastfeeding/feeding practice of mothers are still poor regardless of education level. Nutrition education for breastfeeding mothers is required to encourage good breastfeeding/infant feeding practices.